COST-ORIENTED PRICES TO RENT SPORTS FACILITIES - Dragan Vukasović; Obrad Tadić; Nebojša Malenković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
In order to establish rational pricing policy of renting sports facilities, should examine all relevant factors that influence the price. Market orientation, in determining the objectives of price policy, it must start from their basic goals of policy, such as: the needs of customers and profit. The main goal market orientation is the realization of such a profit that will allow continued expansion of sports facilities and continuously meet the needs of consumers at all higher levels. Pricing policy of renting sports facilities must be both profit-oriented, cost conscious, market-oriented and in line with any other goals you may have a sports agent. Pricing policies and procedures are related to each other and studied together. When we have got a policy objectives of renting sports facilities then we should choose the metod of determining price. Particular attention should be paid to the method of calculating costs. In this paper, we used methods og additional costs.